(untitled) (Biological Sciences - PJSIR, 2008)
. On treating dense conidial suspensions of Aspergillus terreus Thom with different concentrations of Calotropis procera latex, for investigating the genotoxicity of the latter, it was found that latex of Calotropis procera had potent lethal and mutagenic activities. Survival percentage decreased as concentration or time of exposure increased. Frequency of auxotrophic mutants increased with increase in concentration or exposure time. Most auxotrophic mutants were amino acid requiring mutants. DNA and total protein contents of each mutant was significantly lower than wild type of Aspergillus terreus. RAPD demonstrated polymorphic genetic bands of electrophoretic products of PCR for all mutants compared with the wild type strain. SDS-PAGE results expressed a polymorphism of protein bands as well. All these results indicated the mutagenicity of the latex of Calotropis procera.